2016
DOI: 10.3892/or.2016.4912
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-7 promotes angiogenesis in human umbilical vein endothelial cells by upregulating VEGF via KLF4

Abstract: Recent lentiviral-based microRNA (miRNA) library screening has identified miRNA-7 (miR-7) as an anti‑angiogenic miRNA in human umbilical vein endothelial cells (HUVECs). However, the underlying mechanism of miR-7 in the suppression of angiogenesis remains largely unknown. In the present study, we report that miR-7 inhibition promoted angiogenesis by upregulating vascular endothelial growth factor (VEGF) and directly targeting Krüppel-like factor 4 (KLF4). Downregulation of miR-7 promoted tube formation of HUVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Many of these transcriptional regulators are involved in the control of vegfa expression in higher vertebrates 3539 . Amongst those, foxo3 (Forkhead box o3) , a transcriptional repressor of vegfa in cancer cells 25,26 , and klf4 (Krüppel-like factor 4) , a transcriptional activator of vegfa in endothelial cells and a regulator of metastatic processes 27,28 , are known to exert their functions through direct binding to the VegfA promoter 25,27 . In Xenopus somites, their expression is respectively repressed and activated by Etv6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these transcriptional regulators are involved in the control of vegfa expression in higher vertebrates 3539 . Amongst those, foxo3 (Forkhead box o3) , a transcriptional repressor of vegfa in cancer cells 25,26 , and klf4 (Krüppel-like factor 4) , a transcriptional activator of vegfa in endothelial cells and a regulator of metastatic processes 27,28 , are known to exert their functions through direct binding to the VegfA promoter 25,27 . In Xenopus somites, their expression is respectively repressed and activated by Etv6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To allow vegfa expression, Etv6 directly represses foxo3 , a known transcriptional repressor of VegfA in cancer cells 25,26 , thus participating in a double negative gate. Unexpectedly, Etv6 also directly activates expression of klf4 , a known activator of VegfA in endothelial cells and a regulator of metastatic processes 27,28 . Consistent with a feed-forward loop mechanism, Etv6 also binds the vegfa promoter through a Klf4-dependent mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al reported that miR-7 inhibited the tumorigenesis and stemness of prostate cancer via repressing KLF4/PI3K/Akt/p21 pathway [ 41 ]. On the other hand, inhibition of miR-7 was shown to promote angiogenesis in human umbilical vein endothelial cells by up-regulating VEGF via KLF4 [ 22 ]. Consistent with these observations, our data suggested that inhibitory effect on KLF4 expression of miR-7 was significantly mitigated by TINCR in breast cancer via competitive mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…If extrapolated to the in-vivo situation, increased placental miR-10 in IUGR placentas may reflect increased E-cadherin ensuring maturation of cell adhesions towards premature trophoblastic terminal differentiation rather than proliferation, underlying the small sized placentas. On the other hand, KLF4 , a nuclear transcription factor, has been shown to play a number of regulatory roles, including in immune activation, cell growth, and in particular, angiogenesis [6668]. Inhibition of miR-10b led to up-regulation of KLF4 in vitro suggesting that KLF4 suppression as a result of up-regulation of miR-10b in human IUGR placentas in-vivo.…”
Section: Discussionmentioning
confidence: 99%